Penyelesaian Tindak Pidana Penganiayaan Anak Melalui Restorative Justice - Rabbi Faisal; Noenik Soekorini; Sri Astutik (JOURNAL OF SHARIA ECONOMICS, 2022)
Child abuse constitutes a criminal offense that affects not only the physical well-being of children but also their psychological, social, and emotional development. The conventional criminal justice system, which primarily emphasizes punishment, often fails to provide comprehensive recovery for child victims. Consequently, the restorative justice approach has emerged as an alternative mechanism for resolving criminal cases by emphasizing victim recovery, offender accountability, and the restoration of social harmony. This study aims to analyze the mechanism for resolving criminal acts of child abuse through the restorative justice approach and to examine its effectiveness in providing legal protection for child victims. This research employed a normative legal research method using statutory, conceptual, and case approaches. The data consisted of primary, secondary, and tertiary legal materials collected through library research and analyzed qualitatively using a descriptive-analytical method. The findings indicate that the implementation of restorative justice in Indonesia has a solid legal foundation through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Law Number 35 of 2014 concerning Child Protection, Prosecutor Regulation Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice, and National Police Regulation Number 8 of 2021 concerning the Handling of Criminal Cases Based on Restorative Justice. The implementation of this approach has contributed to more victim-oriented case resolution, expedited legal processes, and the restoration of relationships among the parties involved. Nevertheless, its effectiveness is still constrained by inconsistent understanding among law enforcement officers, limited institutional capacity, and insufficient inter-agency coordination. Therefore, strengthening legal regulations, enhancing the capacity of law enforcement officials, and improving institutional coordination are essential to ensure the optimal implementation of the principle of the best interests of the child within Indonesia's criminal justice system.